SCOPING REVIEW : ANALISIS IMPLEMENTASI MAKANAN BERGIZI GRATIS (MBG) DI INDONESIA DAN NEGARA LAIN : STUDI KOMPARATIF BERDASARKAN KEBIJAKAN DAN EFEKTIVITAS PROGRAM - Laeli Desti Rahmawati; Inggar Ratna Kusuma; Fauziyah Luthfi Alya Nabiihah; Nadhif Salwaa Atqiya; Keysha Ayu Annisa Larasati (SINERGI : Jurnal Riset Ilmiah, 2026)
This study aims to analyze and compare the implementation of the Free Nutritious Meal (MBG) Program in Indonesia with similar national school meal programs conducted in India, Ghana, and Scotland. Indonesia’s MBG program, launched in 2024, serves as a strategic initiative to improve students’ nutritional status, reduce stunting, and strengthen human capital development toward Indonesia Emas 2045. However, during its initial phase, the program still faces several challenges, including limited funding, weak inter-agency coordination, uneven distribution of food logistics, and insufficient quality monitoring at school levels.In contrast, India’s Mid-Day Meal Scheme, Ghana’s School Feeding Programme, and Scotland’s Universal Free School Meals policy have demonstrated significant success in improving child nutrition, increasing school attendance, empowering local economies, and ensuring program sustainability. These achievements are supported by stable funding systems, well-structured monitoring mechanisms, and strong collaboration between governments, schools, communities, and the private sector.This research employs a comparative quantitative-descriptive approach using secondary data obtained from academic journals, government reports, and international publications. The analysis evaluates effectiveness indicators such as program coverage, nutritional adequacy, school attendance, and governance quality. The findings reveal significant differences between Indonesia and two reference countries—India and Scotland—yet no significant difference when compared to Ghana. These results indicate that Indonesia must strengthen its funding mechanisms, cross-sectoral coordination, and community participation to enhance the overall performance and sustainability of the MBG program.This study contributes to expanding the understanding of school nutrition policy implementation in Indonesia through lessons learned from international best practices. Furthermore, it underscores the importance of budget transparency, quality control mechanisms, and integrated governance from national to local levels to ensure long-term success of the MBG program.